Rights of LGBTQ+ as a Facet of the Fundamental Right to Liberty and Dignity (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The LGBTQ+ community has historically faced societal discrimination and marginalization, with their fundamental rights often being violated. In recent years, however, there has been a growing recognition of the rights of the LGBTQ+ community, both at the national and international level. This research paper aims to explore the challenges faced by the LGBTQ+ community in India, particularly in the healthcare sector, and the role of human rights in addressing these issues also aims to analyse the legal and social challenges faced by the LGBTQ+ community in India, with a particular focus on the right to liberty and dignity. The paper delves into the historical context, current legal frameworks, and societal attitudes towards the LGBTQ+ community in both countries.